Particulate matter, its production method and use

JP7638966B2Active Publication Date: 2025-03-04BASF SE
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022513494
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-28
Filing Date
2020-08-20
Publication Date
2025-03-04
Estimated Expiration
2040-08-20

Smart Images

  • Figure 0007638966000001
    Figure 0007638966000001
  • Figure 0007638966000002
    Figure 0007638966000002
  • Figure 0007638966000003
    Figure 0007638966000003
Patent Text Reader

Abstract

Composition Li 1+x TM 1-x O2 particulate matter, where x is in the range of 0.1 to 0.2, and TM is a combination of elements according to general formula (I), (Ni a Co b Mn c ) 1-d M 1 d (I) (wherein a is in the range of 0.30 to 0.38, b is in the range of 0 to 0.05, c is in the range of 0.60 to 0.70, d is in the range of 0 to 0.05, M 1 is selected from Al, Ti, Zr, Mo, Mg, B, and a combination of at least two of the above; a+b+c=1) The particulate matter has an average particle size D50 in the range of 2 to 20 μm, and the particulate matter has an average particle size D50 of 2.75 to 3.1 g / cm 3 It has a compressed density in the range of
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to composition Li 1+x TM 1-x With respect to particulate matter of O2, where x is in the range of 0.1 to 0.2, and T is a combination of elements according to general formula (I): (Ni a Co b Mn c ) 1-d M 1 d (I) (In the formula, a is in the range of 0.30 to 0.38, b is in the range of 0 to 0.05, c is in the range of 0.60 to 0.70, d is in the range of 0 to 0.05, M 1 is selected from Al, Ti, Zr, Mo, Mg, B, and a combination of at least two of the above; a+b+c=1) The particulate matter has an average particle size D50 in the range of 2 to 20 μm, and the particulate matter has an average particle size D50 of 2.75 to 3.2 g / cm 3 The compressed density ranges from 100 to 200 mm. [Background technology]

[0002] Lithiated transition metal oxides are currently used as electrode active materials in lithium-ion batteries. Extensive research and development has been carried out over the past few years to improve properties such as charge density, specific energy, as well as other properties such as cycle life degradation and capacity loss that adversely affect the life or applicability of lithium-ion batteries. Further efforts are being made to improve the manufacturing methods.

[0003] Many of the electrode active materials currently discussed are of the lithiated nickel-cobalt-manganese oxide ("NCM material") or lithiated nickel-cobalt-aluminum oxide ("NCA material") type.

[0004] In a typical process for the preparation of cathode materials for lithium-ion batteries, a so-called precursor is first formed by co-precipitation of a transition metal as a carbonate, oxide, or preferably as a hydroxide, which may or may not be basic. This precursor is then mixed with a lithium salt, such as, but not limited to, LiOH, Li2O, or especially Li2CO3, and calcined (fired) at high temperature. The lithium salt(s) can be used as hydrate(s) or in dehydrated form. The calcination or firing, also commonly referred to as thermal or heat treatment of the precursor, is usually carried out at temperatures in the range of 600-1,000°C. During the heat treatment, a solid-state reaction takes place to form the electrode active material. If hydroxides or carbonates are used as precursors, the solid-state reaction is followed by removal of water or carbon dioxide. The heat treatment is carried out in a heated zone of an oven or kiln.

[0005] Extensive research has been conducted into improving various properties of cathode active materials, such as energy density, charge / discharge performance such as capacity fade, etc. However, many cathode active materials suffer from limited cycle life and voltage fade, especially many Mn-rich cathode active materials.

[0006] Certain high manganese materials having high energy density retention are disclosed in EP 3 486 980. However, the disclosed cathode active materials themselves suffer from limited energy density. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] EP 3 486 980 Summary of the Invention [Problem to be solved by the invention]

[0008] It was therefore an object of the present invention to provide a cathode active material having both a high energy density and a high energy density retention. It was a further object of the present invention to provide a method for producing a cathode active material having both a high energy density and a high energy density retention. It was a further object of the present invention to provide a use of a cathode active material having both a high energy density and a high energy density retention. [Means for solving the problem]

[0009] Thus, a particulate material as defined at the outset has been found, which in the following is also referred to as the inventive material or material according to the invention.The inventive material is explained in more detail below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] The substance of the present invention is the composition Li 1+x TM 1-x O2, where x is in the range of 0.1 to 0.2, and T M is a combination of elements according to general formula (I), (Ni a Co b Mn c ) 1-d M 1 d (I) (In the formula, a is in the range of 0.30 to 0.38, b is in the range of 0 to 0.05, and preferably b is 0. c is in the range of 0.60 to 0.70, d is in the range of 0 to 0.05, a+b+c=1, M 1 is selected from Al, Ti, Zr, Mo, Mg, B, and a combination of at least two of the above, and is preferably Al. The particulate matter is 2.75 to 3.2 g / cm 3 , preferably 2.75 to 3.1 g / cm 3 , more preferably 2.80 to 3.10 g / cm 3, and even more preferably 2.85 to 3.10 g / cm 3 It has a compressed density in the range of

[0011] The substances of the invention have an average particle size D50 in the range of 2 to 20 μm, preferably 5 to 16 μm. The average particle size can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles are usually composed of agglomerates from primary particles, and the particle size mentioned above refers to the particle size of the secondary particles.

[0012] In one embodiment of the present invention, the electrode active material of the present invention has a thickness of 0.7 to 4.0 μm. 2 / g or further 6m 2 / g and has a surface area (BET) determined according to DIN-ISO 9277:2003-05 in the range of 1.7 to 3.8 m 2 / g or further 3.0 to 5.5 m 2 / g is preferred.

[0013] Some metals, such as sodium, calcium, or zinc, are ubiquitous and trace amounts of them are present virtually everywhere, but such trace amounts are not considered in the context of this invention, trace amounts in this context meaning amounts of 0.05 mole % or less, based on the total metal content of the TM.

[0014] M 1 may be uniformly or non-uniformly distributed in the particles of the material of the invention. 1 is distributed non-uniformly in the particles of the material of the invention, and even more preferably distributed as a gradient, with M 1 The concentration of is higher in the center of the particle than in the center of the particle.

[0015] In one embodiment of the present invention, the substance of the present invention is composed of spherical particles, which are particles having a spherical shape. Spherical particles include not only those that are precisely spherical, but also particles in which the maximum and minimum diameters of at least 90% (number average) of a representative sample differ by no more than 10%.

[0016] In one embodiment of the invention, the material of the invention is composed of secondary particles which are agglomerates of primary particles. Preferably, the material of the invention is composed of spherical secondary particles which are agglomerates of primary particles. Even more preferably, the material of the invention is composed of spherical secondary particles which are agglomerates of platelet primary particles.

[0017] In one embodiment of the present invention, the primary particles of the substance of the present invention have an average diameter in the range of 1 to 2000 nm, preferably 10 to 1000 nm, particularly preferably 50 to 500 nm. The average diameter of the primary particles can be determined, for example, by SEM or TEM. SEM is the abbreviation for scanning electron microscope and TEM is the abbreviation for transmission electron microscope.

[0018] In one embodiment of the present invention, the volumetric energy density is in the range of 2,750 to 3,100 W·h / l. VED is defined as: VED=1st cycle discharge capacity×average voltage×packed density.

[0019] In one embodiment of the invention the material of the invention has a unimodal particle size distribution, in an alternative embodiment the material of the invention has a bimodal particle size distribution, for example with a maximum in the range 3-6 μm and another maximum in the range 9-12 μm.

[0020] In one embodiment of the invention, the pressed density of the material of the invention, determined at a pressure of 250 MPa, is between 2.75 and 3.1 g / cm 3 The range is 2.85 to 3.10 g / cm 3 is preferred.

[0021] In one embodiment of the invention, the material of the invention has a viscosity of 1.20 to 1.80 g / cm, as determined after 2,000 taps in a graduated cylinder. 3 The tap density ranges from 0.01 to 0.01.

[0022] The materials of the present invention are particularly well suited as cathode active materials since they exhibit both high energy density and high energy density retention.

[0023] A further aspect of the present invention is an electrode comprising at least one cathode active material of the present invention. These are particularly useful in lithium-ion batteries. Lithium-ion batteries comprising at least one electrode according to the present invention show very good discharge and cycle behavior, and they show good safety behavior.

[0024] In one embodiment of the present invention, the cathode of the present invention comprises (A) at least one substance of the invention as described above, (B) carbon in a conductive state, and (C) binder, (D) Current collector Contains:

[0025] In a preferred embodiment of the present invention, the cathode of the present invention comprises, based on the sum of (A), (B) and (C), (A) 80 to 99% by mass of the substance of the present invention; (B) 0.5 to 19.5 mass% carbon, (C) 0.5 to 9.5% by weight of a binder material; Contains:

[0026] The cathode according to the invention contains a conductively modified carbon, also called carbon (B) for simplicity. Carbon (B) can be selected from soot, activated carbon, carbon nanotubes, graphene, and graphite. Carbon (B) can be added directly during the preparation of the electrode material according to the invention.

[0027] The electrodes according to the invention may contain further components. They may contain a current collector (D), for example (but not limited to) an aluminum foil. They may further contain a binder material (C), also called binder (C) below. The current collector (D) will not be described further here.

[0028] Suitable binders (C) are preferably selected from organic (co)polymers.Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene.Polypropylene is also suitable.Polyisoprene and polyacrylates are furthermore suitable.Polyacrylonitrile is particularly preferred.

[0029] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or with styrene. Polyacrylonitrile homopolymers are preferred.

[0030] In the context of the present invention, polyethylene refers not only to homopolyethylenes, but also to copolymerized ethylene with at least 50 mol % and up to 50 mol % of at least one further comonomer, such as α-olefins, such as propylene, butylene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and also isobutene, vinyl aromatics, such as styrene, and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C2 copolymers of (meth)acrylic acid. 10 -alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also copolymers of ethylene with maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.

[0031] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene but also copolymers of propylene with at least 50 mol % copolymerized propylene and up to 50 mol % of at least one further comonomer, such as ethylene, and α-olefins, such as butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic polypropylene or essentially isotactic polypropylene.

[0032] In the context of the present invention, polystyrene refers not only to homopolymers of styrene, but also to C1-C4 copolymers of acrylonitrile, 1,3-butadiene, (meth)acrylic acid, and (meth)acrylic acid. 10 -alkyl esters, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene copolymers are also understood to mean.

[0033] Another preferred binder (C) is polybutadiene.

[0034] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimides and polyvinyl alcohol.

[0035] In one embodiment of the invention, the binder (C) has an average molecular weight M ranging from 50,000 g / mol to 1,000,000 g / mol, preferably up to 500,000 g / mol. W The (co)polymers are selected from those having the formula:

[0036] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.

[0037] In a particularly preferred embodiment of the present invention, the binder (C) is selected from halogenated (co)polymers, in particular fluorinated (co)polymers.Halogenated or fluorinated (co)polymers are understood to mean (co)polymers that contain at least one (co)polymerized (co)monomer with at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule.Examples include polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and ethylene-chlorofluoroethylene copolymer.

[0038] Suitable binders (C) are especially polyvinyl alcohol and halogenated (co)polymers such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride and especially polyvinylidene fluoride and polytetrafluoroethylene.

[0039] The electrode of the present invention may contain 0.5 to 9.5 mass % of binder(s) (C) based on the total mass of the component (A), carbon (B) and binder (C).

[0040] A further aspect of the present invention is (1) at least one cathode comprising the material of the present invention (A), carbon (B) and a binder (C); (2) at least one anode; and (3) at least one electrolyte It is a battery containing

[0041] The embodiment of the cathode (1) has already been described in detail above.

[0042] The anode (2) may contain at least one anode active material, such as carbon (graphite), TiO2, lithium titanium oxide, silicon, or tin. The anode (2) may further contain a current collector, such as a metal foil, such as copper foil.

[0043] The electrolyte (3) may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally additives.

[0044] The non-aqueous solvent for the electrolyte (3) may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.

[0045] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C1-C4-alkylene glycols and in particular polyethylene glycols, where the polyethylene glycols may contain up to 20 mol % of one or more C1-C4-alkylene glycols. The polyalkylene glycols are preferably polyalkylene glycols with two methyl or ethyl end caps.

[0046] The molecular weight M of suitable polyalkylene glycols and particularly suitable polyethylene glycols W may be at least 400 g / mol.

[0047] The molecular weight M of suitable polyalkylene glycols and particularly suitable polyethylene glycols W can be up to 5,000,000 g / mol, preferably up to 2,000,000 g / mol.

[0048] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, preferably 1,2-dimethoxyethane.

[0049] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.

[0050] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.

[0051] An example of a suitable cyclic acetal is 1,3-dioxane, and especially 1,3-dioxolane.

[0052] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0053] Examples of suitable cyclic organic carbonates are those represented by the general formulas (II) and (III):

[0054] [ka]

[0055] (In the formula, R 1 , R 2 and R 3 can be the same or different and are selected from hydrogen and C1-C4-alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, preferably R 2 and R 3 (Both cannot be tert-butyl) It is a compound of the formula:

[0056] In a particularly preferred embodiment, R 1 is methyl, R 2 and R 3 are each hydrogen or R1 , R 2 and R 3 are hydrogen.

[0057] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV).

[0058] [ka]

[0059] Preferably, the solvent or solvents are used in an aqueous state, ie with a water content in the range of 1 ppm to 0.1% by weight, which can be determined, for example, by Karl Fischer titration.

[0060] The electrolyte (3) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imide, e.g. LiN(C n F 2n+1 SO2)2 (wherein n is an integer ranging from 1 to 20), LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4, and compounds of the general formula (C n F 2n+1 SO2) t Salt of YLi where t=1 when Y is selected from oxygen and sulfur; when Y is selected from nitrogen and phosphorus, t=2; When Y is selected from carbon and silicon, t=3).

[0061] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, particularly preferred are LiPF6 and LiN(CF3SO2)2.

[0062] In a preferred embodiment of the present invention, the electrolyte (3) contains at least one flame retardant. Useful flame retardants can be selected from trialkyl phosphates (wherein the alkyls are different or the same), triallyl phosphates, alkyl dialkyl phosphonates, and halogenated trialkyl phosphates. Preference is given to tri-C1-C4-alkyl phosphates (wherein the C1-C4-alkyls are different or the same), tribenzyl phosphate, triphenyl phosphate, C1-C4-alkyl, di-C1-C4-alkyl phosphonates, and fluorinated tri-C1-C4-alkyl phosphates.

[0063] In a preferred embodiment, the electrolyte (3) comprises at least one flame retardant selected from trimethyl phosphate, CH3-P(O)(OCH3)2, triphenyl phosphate, and tris-(2,2,2-trifluoroethyl)-phosphate.

[0064] The electrolyte (3) may contain 1 to 10 mass % of a flame retardant based on the total mass of the electrolyte.

[0065] In one embodiment of the invention, the battery according to the invention comprises one or more separators (4) by means of which the electrodes are mechanically separated. Suitable separators (4) are polymer films, in particular porous polymer films, which are non-reactive towards metallic lithium. Particularly suitable materials for the separators (4) are polyolefins, in particular film-forming porous polyethylene and film-forming porous polypropylene.

[0066] The separator (4) made of polyolefin, particularly polyethylene or polypropylene, can have a porosity in the range of 35 to 50%. The suitable pore size is, for example, in the range of 30 to 500 nm.

[0067] In another embodiment of the present invention, the separator (4) can be selected from PET nonwoven fabrics filled with inorganic particles. Such separators can have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.

[0068] The battery according to the invention may further comprise a housing which may have any shape, for example that of a cube or a cylindrical disk. In one variant, a metal foil configured as a pouch is used as the housing.

[0069] The battery according to the invention exhibits very good discharge and cycling behaviour, especially with regard to capacity loss, especially at high temperatures (above 45° C., for example up to 60° C.).

[0070] The battery according to the invention may comprise two or more electrochemical cells that are combined with each other, for example connected in series or connected in parallel. A series connection is preferred. In the battery according to the invention, at least one electrochemical cell contains at least one electrode according to the invention. Preferably, in the electrochemical cell according to the invention, the majority of the electrochemical cells contain electrodes according to the invention. Even more preferably, in the battery according to the invention, all electrochemical cells contain electrodes according to the invention.

[0071] The present invention further provides a method for using the battery according to the present invention in equipment, especially mobile equipment.Examples of mobile equipment are vehicles, such as automobiles, bicycles, aircraft, or water vehicles, such as boats or ships.Other examples of mobile equipment are manually operated, such as computers, especially laptops, phones, or powered hand tools, for example in the construction sector, especially drills, battery-powered drivers, or battery-powered staplers.

[0072] Another aspect of the present invention relates to a method for producing the substance of the present invention, which method is also referred to as the "method of the present invention". The method of the present invention comprises the following steps: (a) Manganese, Nickel, and optionally Co and M 1providing a particulate hydroxide, oxide or oxyhydroxide of at least one element of (b) adding a lithium source; (c) heat treating the mixture resulting from step (b); (d) lithiated the resulting oxide with a mineral acid or M 1 or a combination thereof; (e) removing water; (f) heat treating the resulting solid residue; Includes.

[0073] The method of the present invention comprises six steps (a), (b), (c), (d), (e) and (f), which are also referred to in the context of the present invention as steps (a), (b), (c), (d), (e) and (f), respectively. The initiation of steps (d) and (e) may be simultaneous or preferably successive. Steps (d) and (e) may be performed simultaneously or successively, preferably with at least partial overlap or simultaneously. During step (f), some water in the form of residual moisture may also be removed. Step (d) is performed after the completion of step (c).

[0074] Each step will be described in more detail below.

[0075] In step (a), manganese, nickel and optionally Co and M 1 A particulate hydroxide, oxide or oxyhydroxide (hereinafter also referred to as "precursor") is provided, which comprises manganese, nickel and, optionally, Co and M. 1 The hydroxides of at least one of the elements can be obtained, for example, from the respective sulfates by coprecipitation with sodium hydroxide or potassium hydroxide.

[0076] In one embodiment of the invention, the precursor has an average particle size D50 in the range of 2 to 20 μm, preferably 6 to 15 μm. Average particle size D50 in the context of the present invention refers to the median particle size based on volume, as can be determined, for example, by light scattering.

[0077] In one embodiment of the invention, the width of the particle size distribution of the precursor, expressed as [(d90-d10) / (d50) diameter], is at least 0.61, for example from 0.61 to 2, preferably from 0.65 to 1.5.

[0078] In one embodiment of the present invention, M 1 contains Mg in the range of 0.1 to 2.5 mol % based on the total metals in the precursor.

[0079] In one embodiment of the invention, the precursor has 0.01 to 10 mol %, preferably 0.3 to 5 mol %, of anions other than hydroxide ions or carbonate ions, for example sulfate ions, based on the total number of anions.

[0080] In one embodiment of the invention, the precursor comprises manganese, nickel, and optionally cobalt and M. 1 It is prepared by combining an aqueous solution of a water-soluble salt of (solution (α)) with an aqueous solution of sodium hydroxide or potassium hydroxide (solution (β)).

[0081] The term water-soluble salts of manganese and nickel, or of metals other than nickel and manganese, refers to salts that have a solubility in distilled water of 25 g / l or more at 25° C., the amount of salt being determined omitting water of crystallization and water resulting from aquo complexes. The water-soluble salts of nickel, cobalt and manganese are preferably Ni 2+ and Mn 2+ Examples of the water-soluble salts of nickel and manganese include sulfates, nitrates, acetates, and halides (particularly chlorides). Nitrates and sulfates are preferred, and sulfates are more preferred.

[0082] In one embodiment of the present invention, the concentration of solution (α) can be selected within a wide range. Preferably, the total concentration is selected to be in the range of 1 to 1.8 moles of transition metal per kg of solution, more preferably in the range of 1.5 to 1.7 moles of transition metal per kg of solution. As used herein, "transition metal salt" refers to nickel and manganese, and, where applicable, cobalt and M. 1 and may include salts of other metals, such as magnesium or aluminum, or salts of transition metals other than nickel and manganese.

[0083] Another example of a water-soluble salt is alum, KAl(SO4)2.

[0084] Solution (α) may have a pH value in the range of 2 to 5. In embodiments where a higher pH value is desired, ammonia may be added to solution (α). However, it is preferred not to add ammonia.

[0085] Solution (β) is an aqueous solution of sodium hydroxide or potassium hydroxide, such as potassium hydroxide and a combination of sodium hydroxide and potassium hydroxide, with sodium hydroxide being even more preferred.

[0086] Solution (β) may contain some amount of carbonate, for example due to aging of the solution or the respective alkali metal hydroxide.

[0087] The pH value of the solution (β) is preferably greater than or equal to 13, for example 14.5.

[0088] It is preferred that no ammonia be used in the step of combining solutions (α) and (β).

[0089] In one embodiment of the present invention, the pH value at the end of the step of combining solutions (α) and (β), each measured in the mother liquor at 23° C., is in the range of 8 to 12, preferably 10.5 to 12.0, more preferably 11.0 to 12.0.

[0090] In one embodiment of the present invention, the coprecipitation is carried out at a temperature in the range of 10 to 85°C, preferably in the range of 20 to 60°C.

[0091] In one embodiment of the invention, the co-precipitation is carried out under an inert gas, for example a noble gas such as argon, or N2.

[0092] In one embodiment of the invention, a slight excess of hydroxide is applied, for example 0.1 to 10 mol %.

[0093] During the combination of solutions (α) and (β) a slurry is formed. The solids may be separated by solid-liquid separation techniques, such as decantation, filtration and by means of a centrifuge, with filtration being preferred. A precursor is obtained. The precursor is then dried, for example under air, at a temperature in the range of 100-120° C. Preferably, the residual water content of the precursor is less than or equal to 1% by weight, for example 0.01-0.5% by weight.

[0094] In step (b), a lithium source is added to the precursor. To carry out step (b) of the method of the present invention, the procedure is, for example, to mix the precursor with at least one lithium compound selected from Li2O, LiOH and Li2CO3, the water of crystallization being ignored in the context of the present invention. The preferred lithium source is Li2CO3.

[0095] To carry out step (b), the amounts of precursor and lithium source are selected to obtain the desired stoichiometry of the material of the invention. Preferably, the precursor and source of lithium compound(s) are selected such that the molar ratio of lithium to the sum of all transition metals and any M is in the range of 1.275:1 to 1.42:1, preferably 1.30:1 to 1.38:1, even more preferably 1.32:1 to 1.36:1.

[0096] Step (b) can be carried out, for example, in a ploughshare mixer or a tumble mixer. In laboratory scale experiments, it is also possible to apply a roller mill.

[0097] To carry out step (c) of the process of the present invention, the mixture obtained according to step (c) is calcined at a temperature in the range of 650-1000°C, preferably 875-950°C.

[0098] Step (c) of the process of the invention can be carried out in a furnace, such as a rotary tube furnace, a muffle furnace, a pendulum furnace, a roller hearth furnace or a push-through furnace, also a combination of two or more of said furnaces is possible.

[0099] Step (c) of the method of the invention can be carried out for a period of between 30 minutes and 24 hours, preferably between 3 and 12 hours. Step (c) can be carried out at a temperature level or a temperature profile can be carried out.

[0100] In one embodiment of the present invention, step (c) is carried out in an oxygen-containing atmosphere, which includes air, pure oxygen, a mixture of oxygen and air, and air diluted with an inert gas such as nitrogen. In step (c), an oxygen atmosphere or an oxygen atmosphere diluted with air or nitrogen is preferred, with a minimum oxygen content of 21% by volume.

[0101] In one embodiment of the present invention, between steps (b) and (c), at least one precalcination step (c * ) is being carried out. * ) involves heating the mixture obtained in step (b) at a temperature in the range of 300-700° C. for 2-24 hours.

[0102] During the temperature change, a heating rate of 1 K / min to 10 K / min can be obtained, preferably 2 to 5 K / min.

[0103] After step (c), the resulting material is preferably cooled to room temperature.

[0104] In step (d), the particulate matter is 1or a combination thereof, preferably an aqueous solution of an inorganic aluminium compound. The aqueous solution may have a pH value ranging from 1 to 8, preferably at least 2, more preferably from 2 to 7. At the end of step (d), the pH value of the aqueous phase is preferably observed to be in the range of 3 to 6.

[0105] Examples of mineral acids are nitric acid, especially sulfuric acid, for example at a concentration of 0.01M to 2M, preferably 0.1 to 1.5M.

[0106] Preferably, the water hardness, in particular calcium, of the aqueous solution used in step (d) is at least partially removed. It is preferred to use demineralized water.

[0107] Such an M 1 The compound is readily soluble in water. "Readily soluble" in this context means that the compound has a molecular weight of at least 10 g M per liter of water at 25°C. 1 This means the solubility of a compound in water.

[0108] Examples of suitable aluminum compounds are Al2(SO4)3, KAl(SO4)2, and Al(NO3)3.

[0109] An example of a suitable titanium compound is Ti(SO4)2. An example of a suitable zirconium compound is zirconium nitrate, which has the empirical formula Zr(NO3)4.

[0110] Examples of suitable molybdenum compounds are MoO3, Na2MoO4, and Li2MoO4.

[0111] Examples of suitable magnesium compounds are MgSO4, MgCl2, and Mg(NO3)2.

[0112] An example of a suitable boron compound is boric acid, which has the empirical formula H3BO3.

[0113] In one embodiment of the present invention, M 1The amount of this compound is in the range of 0.01 to 5.0 mol %, preferably 0.1 to 2.0 mol %, based on TM.

[0114] In one embodiment of the present invention, the treatment comprises the step of: 1 This is carried out using a solution of this compound, for example a solution of Al2(SO4)3 in aqueous H2SO4.

[0115] The treatment in step (d) comprises treating the cathode active material of step (c) with a mineral acid or M 1 and allowing the resulting mixture to interact, which may be facilitated by stirring.

[0116] In one embodiment of the present invention, step (d) is carried out at a temperature in the range of 5 to 85° C., preferably 10 to 60° C. Room temperature is particularly preferred.

[0117] In one embodiment of the invention, step (d) is carried out at normal pressure. However, it is preferred to carry out step (d) under elevated pressure, for example at a pressure between 10 mbar and 10 bar above normal pressure, or under suction, for example at a pressure between 50 and 250 mbar below normal pressure, preferably at a pressure between 100 and 200 mbar below normal pressure.

[0118] In one embodiment of the invention, step (d) is carried out in an agitated filter apparatus, such as an agitated pressure filter or an agitated suction filter.

[0119] The material obtained from step (c) is called M 1 The duration of treatment with the compound may range from 2 to 60 minutes, preferably from 10 to 45 minutes.

[0120] In one embodiment of the present invention, the material obtained from step (c) is reacted with a mineral acid or M 1 The volume ratio of each of the compounds to the solution is in the range of 1:1 to 1:10, preferably 1:1 to 1:5.

[0121] In one embodiment of the invention, steps (d) to (e) are carried out in the same vessel, for example an agitated filter apparatus, such as an agitated pressure filter or an agitated suction filter.

[0122] In one embodiment of the present invention, step (d) is repeated, for example, from 1 to 10 times. In a preferred embodiment, step (d) is carried out only once.

[0123] In step (e), water is removed. Said removal of water may be carried out by evaporation or, preferably, by a solid-liquid separation method, such as decantation, or by any type of filtration, for example, by a band filter or a filter press. Step (e) may involve complete or partial removal of water, with partial removal being preferred. Together with the water, mineral acid and / or unprecipitated M 1 The compound and / or lithium salt may be removed, and a residue is obtained which may contain 0.01 to 5% by mass of residual moisture.

[0124] In one embodiment of the present invention, the filter media may be selected from ceramics, sintered glass, sintered metals, organic polymer films, nonwoven fabrics, and woven fabrics.

[0125] In step (f), the residue is heat treated.

[0126] Step (f) may be carried out in any type of oven, such as a roller hearth kiln, a pusher kiln, a rotary kiln, a pendulum kiln, or in laboratory scale tests, a muffle oven.

[0127] The temperature of the heat treatment in step (f) may be in the range of 150 to 290°C, or 300 to 500°C.

[0128] The temperature of 300 to 500° C. corresponds to the maximum temperature of step (f).

[0129] It is possible for the material obtained from step (e) to be subjected directly to step (f), however it is preferred to stepwise increase or ramp up the temperature or to first dry the material obtained after step (e) at a temperature in the range of 40-80° C. before subjecting it to step (f).

[0130] The stepwise temperature increase or ramp-up can be carried out at normal pressure or reduced pressure, for example, at a pressure of 1 to 500 mbar.

[0131] Step (f) at the maximum temperature may be carried out under normal pressure.

[0132] In one embodiment of the invention, step (f) is carried out under an oxygen-containing atmosphere, such as air, oxygen-enriched air or pure oxygen.

[0133] In embodiments where step (f) is preceded by drying at a temperature in the range of 100-250° C., such drying may be carried out for a duration of 10 minutes to 12 hours.

[0134] In one embodiment of the present invention, step (f) is carried out under an atmosphere having a reduced CO2 content, for example, a carbon dioxide content in the range of 0.01 to 500 ppm by mass, preferably 0.1 to 50 ppm by mass. The CO2 content can be determined, for example, by an optical method using infrared light. It is further preferred to carry out step (f) under an atmosphere having a carbon dioxide content below the detection limit, for example, by an optical method based on infrared light.

[0135] In one embodiment of the invention, step (f) has a duration ranging from 1 to 10 hours, preferably from 90 minutes to 6 hours.

[0136] In one embodiment of the present invention, the lithium content of the electrode active material is reduced by 1 to 5% by mass, preferably by 2 to 4% by mass, said reduction mainly affecting the so-called residual lithium.

[0137] By carrying out the method of the present invention, an electrode active material having superior electrochemical properties is obtained. Without wishing to be bound by any theory, it is hypothesized that the excess aluminum leads to the trapping of lithium compounds that are deposited on the surface of the electrode active material.

[0138] Without wishing to be bound by any theory, it is hypothesized that the method of the present invention results in modification of the surface of particles of the material of the present invention.

[0139] The method of the invention may comprise further (optional) steps, such as a washing step after step (e) or a sieving step after step (f).

[0140] The present invention is further illustrated by examples. EXAMPLES

[0141] General Notes: Unless otherwise stated, percentages are by weight.

[0142] ICP: Inductively Coupled Plasma The compressed density was measured at 250 MPa.

[0143] I. Synthesis of the Materials of the Invention I.1 Synthesis of precursors All coprecipitations were carried out under an atmosphere of N2.

[0144] I.1.1 Synthesis of TM-OH.1, step (a.1) A stirred tank reactor was charged with deionized water and heated to 45° C. The pH value was then adjusted to 11.3 by adding aqueous sodium hydroxide solution.

[0145] The coprecipitation reaction was started by simultaneously feeding aqueous solutions of transition metal sulfate and sodium hydroxide at a flow ratio of 1.9 with a total flow rate of 12 hours average residence time. The transition metal solution contained Ni and Mn in a molar ratio of 1:2 and a total transition metal concentration of 1.65 mol / kg. The aqueous sodium hydroxide solution was a 50% by weight solution of sodium hydroxide. The pH value was maintained at 11.3 by separately feeding aqueous sodium hydroxide. Starting from the start of all feeds, the mother liquor was continuously removed. After 29 hours, all feed flows were stopped. The resulting suspension was filtered, washed with distilled water, dried at 120°C in air and sieved to obtain the mixed transition metal (TM) oxyhydroxide precursor. The precursor TM-OH.1 was obtained with an average particle size (D50) of 6 μm.

[0146] I.1.2 Synthesis of TM-OH.2, step (a.2) The protocol of I.1 was basically followed, but first ammonia was added, 18 g ammonium sulfate per kg water. During the coprecipitation, 28% by mass ammonium hydroxide solution was fed at a flow rate ratio of 0.09 (per kg sodium hydroxide solution). The precursor TM-OH.2 with an average particle size (D50) of 6 μm was obtained.

[0147] I.2 Synthesis of Untreated Cathode Active Material, Steps (b) and (c) I.2.1 Synthesis of the base BM.1 The precursors TM-OH.1 and Li2CO3 were mixed in a Li / (TM) molar ratio of 1.15. The resulting mixture was heated to 970 °C and kept for 5 h under a forced flow of a mixture of 20% oxygen and 80% nitrogen (by volume). After cooling to room temperature, the powder was deagglomerated and sieved through a 32 μm mesh to obtain the base material BM.1. The surface area (BET) was 1.42 m 2 / g and the compressed density is 2.92 g / cm 3 It was.

[0148] I.2.2 Synthesis of base BM.2 The precursors TM-OH.1 and Li2CO3 were mixed in a Li / (TM) molar ratio of 1.14. The resulting mixture was heated to 875 °C and kept for 5 h under a forced flow of a mixture of 20% oxygen and 80% nitrogen (by volume). After cooling to room temperature, the powder was deagglomerated and sieved through a 32 μm mesh to obtain the base material BM.1. The surface area (BET) was 1.94 m 2 / g and the compressed density is 2.88g / cm 3 It was.

[0149] I.2.3 Synthesis of base BM.3 The precursors TM-OH.2 and Li2CO3 were mixed in a Li / (TM) molar ratio of 1.14. The resulting mixture was heated to 925 °C and kept for 5 h under a forced flow of a mixture of 20% oxygen and 80% nitrogen (by volume). After cooling to room temperature, the powder was deagglomerated and sieved through a 32 μm mesh to obtain the base material BM.3. The surface area (BET) was 1.14 m 2 / g and the compressed density is 2.99g / cm 3 It was.

[0150] I.2.4 Synthesis of base BM.4 The precursors TM-OH.2 and Li2CO3 were mixed in a Li / (TM) molar ratio of 1.17. The resulting mixture was heated to 950 °C and kept for 5 h under a forced flow of a mixture of 20% oxygen and 80% nitrogen (by volume). After cooling to room temperature, the powder was deagglomerated and sieved through a 32 μm mesh to obtain the base material BM.4. The surface area (BET) was 1.11 m 2 / g and the compressed density is 3.08g / cm 3 It was.

[0151] I.2.5 Synthesis of base BM.5 The precursors TM-OH.1 and Li2CO3 were mixed in a Li / (TM) molar ratio of 1.16. The resulting mixture was heated to 950 °C and kept for 5 h under a forced flow of a mixture of 20% oxygen and 80% nitrogen (by volume). After cooling to room temperature, the powder was deagglomerated and sieved through a 32 μm mesh to obtain the base material BM.5. The surface area (BET) was 1.36 m 2 / g and the compressed density is 3.05g / cm3 It was.

[0152] I.3 Treatment of the basic material with a mineral acid, step (d), removal of water, step (e), and heat treatment, step (f). I.3.1 Basic Protocol General method, step (d.1): 1 kg of BM.1 was placed in a tank reactor equipped with a magnetic stirrer. 25.5 g of Al2(SO4)3 was dissolved in 4 liters of 0.1 M H2SO4, diluted with 1 liter of water and added to BM.1. The resulting slurry was stirred at room temperature for 30 minutes, step (d.1).

[0153] The liquid phase was then removed by filtration, step (e.1).

[0154] The filter cake was washed with 4 liters of water.

[0155] Step (f.1): The obtained filter cake was first dried at 120°C in vacuum for 12 hours, then heat-treated in an electric furnace at 400°C for 5 hours in an atmosphere of 60% by volume of oxygen (remainder: nitrogen), then cooled to room temperature and sieved through a 32 μm mesh to obtain the material CAM.1 of the present invention.

[0156] Table 1 summarizes the process parameters. Table 2 summarizes the physical and chemical analytical parameters.

[0157] [Table 1]

[0158] II. Cathode Active Material Testing II.1 Electrode fabrication, general procedure Cathode: PVDF binder (Solef® 5130) was dissolved in NMP (Merck) to make a 10 wt% solution. For electrode preparation, the binder solution (3.5 wt%), graphite (KS6, 2 wt%) and carbon black (Super C65, 2 wt%) were suspended in NMP. After mixing using a planetary centrifugal mixer (ARE-250, Thinky Corporation; Japan), either the inventive CAM.1-CAM.5 or the comparative cathode active material (92.5 wt%) was added and the suspension was mixed again to obtain a lump-free slurry. The solids content of this slurry was adjusted to 62.3%. This slurry was coated on Al foil using an Erichsen autocoater. All electrodes were calendered before further use. The thickness of the cathode material was 38 μm, with a density of 9 mg / cm. 2 Prior to cell assembly, all electrodes were dried at 105 °C for 12 h.

[0159] II.2 Electrolyte production A basic electrolyte composition was prepared containing 1M LiPF6, 1:4 (w / w) fluoroethylene carbonate:diethyl carbonate.

[0160] II.3 Manufacturing of coin-type half cells Coin-shaped half-cells (20 mm diameter, 3.2 mm thickness) containing the cathode prepared as described in II.1 and lithium metal as working and counter electrodes were assembled and sealed in an Ar-filled glove box. The cathode, anode, and separator were then stacked in the following order: cathode / separator / Li foil to prepare a half-coin cell. Then, 0.15 mL of EL base 1 described above (III.2) was introduced into the coin cell.

[0161] IV. Cell performance evaluation Coin-type half-cell performance evaluation The battery performance of the produced coin-type battery was evaluated by measuring the initial capacity and reaction resistance of the cell.

[0162] Initial performance and cycling were measured as follows: The coin half-cell according to II.3 was tested at room temperature and at voltages ranging between 4.8 V and 2.0 V. For the initial cycle, the initial lithiation was performed in CC-CV mode, i.e., a constant current (CC) of 0.067 C was applied until 0.01 V was reached. After a rest period of 5 minutes, reduction lithiation was performed at a constant current of 0.067 C up to 2.0 V. The results are summarized in Table 2.

[0163] [Table 2]

[0164] DC: discharge capacity CE: Coulombic efficiency VED: Volumetric energy density nd:Undecided The first cycle charge capacity was 248 mA·h / g for BM.2 and 262 mA·h / g for CAM.2.

[0165] BM.1, BM.2, BM.3, BM.4, and BM.5 were used as comparative substances.

Claims

1. A method for producing a particulate matter, comprising the steps of: (a) Manganese, nickel, Co and M, prepared by coprecipitation with sodium hydroxide as a base. 1 providing a particulate hydroxide, oxide or oxyhydroxide with at least one of (b) adding a lithium source; (c) heat treating the mixture resulting from step (b); (d) The resulting lithiated oxide is dissolved in a mineral acid or M 1 or combinations thereof at a pH value in the range of 1 to 7; (e) removing water; (f) heat treating the resulting solid residue; Including, No ammonia or ammonium sulfate is added, said particulate matter being of the composition Li 1+x TM 1-x O 2 , where x is in the range of 0.1 to 0.2 and TM is a combination of elements according to general formula (I); (Ni a Co b Mn c ) 1-d M 1 d (I) (wherein a is in the range of 0.30 to 0.38; b is in the range of more than 0 to 0.05; c is in the range of 0.60 to 0.70; 0<d≦0.05; M 1 is Al; a + b + c = 1) The particulate matter has an average particle size D50 in the range of 2 to 20 μm, the particulate material has a compressed density, determined at a pressure of 250 MPa, in the range of 2.85 to 3.10 g / cm 3 ; and A method wherein the particulate matter has a surface area BET in the range of 3.0 to 5.5 m 2 / g.

2. The method of claim 1, wherein step (c) is carried out at a maximum temperature in the range of 650 to 1000°C.

3. 3. The process according to claim 1 or 2, wherein step (e) is carried out by a solid-liquid separation step.

4. The method according to any one of claims 1 to 3, wherein step (f) is carried out at a temperature in the range of 300 to 500°C.

5. 5. The method according to claim 1, wherein steps (d) and (e) are carried out simultaneously.

Citation Information

Patent Citations

  • Twin-spherical lithium-rich cathode material of lithium ion secondary battery and preparation method thereof

    CN105047898A

  • Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery

    EP3486980A1

  • Positive electrode active material used for nonaqueous electrolyte secondary battery, and method for producing the same

    JP2012079703A

  • Method for producing lithium-containing compound oxide, positive electrode for lithium ion secondary battery and lithium ion secondary battery

    JP2016017017A

  • Lithium secondary battery

    JP2016167446A